Penerapan Problem-Based Learning untuk Meningkatkan Hasil Belajar di Sekolah Menengah Atas - Siti Rumaidah; Taufiqur Rahman (Jurnal Pendidikan Islam Indonesia, 2020)
Traditional instruction limited students' autonomy to construct their own knowledge. This condition enforce students' dependency to the teacher. Consequently, it affects their learning outcomes. an effort to improve the learning outcomes by applying problem-based learning model is supported by several researches. This study deployed action research design carried in two circle. The result stated that there are improvements in three aspect i.e attitude, knowledge and skill. Average score of attitude aspect increase from 77,48 to 77,86; knowledge aspect from 77,26 to 77,98; skill aspect from 76,52 to 77,80. Number of students achieving classical mastery learning criteria increase 20% from first circle i.e 64% of 25 students. Therefore, the criteria is achieved. The result also points that learning task carried by small group make knowledge transfer as learning community possible.